The development of the emerging technologies sustainability assessment (ETSA) and its application in the design of a bioprocess for the treatment of wine distillery effluent - Khan, Nuraan (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
Emerging Technologies Sustainability Assessment (ETSA) is a new technology assessment tool that was developed in order to compare emerging processes or technologies to existing alternatives. It utilizes infoIDlation modules, with the minimum use of resources such as time and money, in order to deteIDline if the process under development is comparatively favourable and should be developed beyond the early conceptual phase. The preliminary ETSA is vital in order to identify the gaps in the existing information and the specific methodologies to be used for data capture and analysis. The use of experimental design tools, such as Design-Expert, can facilitate rapid and efficient collection of necessary data and fits in well with the rationale for the ETSA. Wine distillery effluent (vinasse) is the residue left after alcohol has been distilled from fennented grape juice. It is an acidic, darkly coloured effluent, with a high COD and polyphenol content. The most popular method of disposal of this effluent, land application, is no longer viable due to stricter legislation and pressure on the industry to better manage its wastes. Although the ability of whiterot fungi to degrade a number of pollutants is well-known, fungal treatment of wine distillery effluent is still in the conceptual phase. The perfoIDlance of the fungal remediation system was assessed experimentally in terms of COD removal and laccase production using Design-Expert. Although Pycnoporus sanguine us was found to be most efficient at COD removal (85%) from 30% vinasse, laccase production was low (0.021 U/I). The optimum design for economically viable fungal treatment used Trametespubescens. This fungus was able to remove over 50% of the COD from undiluted vinasse while producing almost 800U/l of the valuable laccase enzyme within three days. Since the effluent from the fungal system did not meet the legal limits for wastewater disposal, a two-stage aerobicanaerobic system is suggested to improve the quality of the effluent prior to disposal. The ETSA was used to assess the fungal technology in relation to the two current methods of vinasse treatment and disposal, namely land application and anaerobic digestion. Based on the ETSA, which considered environmental, social and economic impacts, the fungal system proved to be potentially competitive and further development of the technology is suggested.
Keywords: Technology assessment; Wine and wine making -- Waste disposal; Distilleries -- Waste disposal